Lipid Metabolism in Neurons: A Brief Story of a Novel c-Fos-Dependent Mechanism for the Regulation of Their Synthesis - Rodríguez-Berdini, Lucia; Caputto, Beatriz L. (Frontiers in Cellular Neuroscience, 2019)
The mechanisms that coordinately regulate lipid synthesis in the nervous system together with the high rates of membrane biogenesis needed to support cell growth are largely unknown as are their subcellular site of synthesis. c-Fos, a well-known AP-1 transcription factor, has emerged as a unique protein with the capacity to associate to specific enzymes of the pathway of synthesis of phospholipids at the endoplasmic reticulum and activate their synthesis to accompany genomic decisions of growth. Herein, we discuss this effect of c-Fos in the context of neuronal differentiation and also with respect to pathologies of the nervous system such as the development and growth of tumors. We also provide insights into the sub-cellular sites where this regulation occurs at the endoplasmic reticulum membranes and the molecular mechanism by which c-Fos exerts this activity.